One‐Pot Green Process to Synthesize MXene with Controllable Surface Terminations using Molten Salts. (10th November 2021) - Shen, Miao; Jiang, Weiyan; Liang, Kun; Zhao, Sufang; Tang, Rui; Zhang, Linjuan; Wang, Jian‐Qiang
Abstract: Surface terminations of two‐dimensional MXene (Ti3 C2 T x ) considerably impact its physicochemical properties. Commonly used etching methods usually introduce ‐F surface terminations or metallic impurities in MXene. We present a new molten‐salt‐assisted electrochemical etching method to synthesize fluorine‐free Ti3 C2 Cl2 . Using electrons as reaction agents, cathode reduction and anode etching can be spatially isolated; thus, no metallics are present in the Ti3 C2 Cl2 product. The surface terminations can be in situ modified from −Cl to −O and/or −S, which considerably shortens the modification steps and enriches the variety of surface terminations. The obtained −O‐terminated Ti3 C2 T x are excellent electrode materials for supercapacitors, exhibiting capacitances of 225 F g −1 at 1.0 Ag −1, good rate performance (91.1 % at 10 Ag −1 ), and excellent capacitance retention (100 % after 10000 charge/discharge cycles at 10 Ag −1 ), which is superior to multi‐layered Ti3 C2 T x prepared by other etching methods. Abstract : This is the first study to use a molten‐salt‐assisted electrochemical etching (MS‐E‐etching) method to synthesize Ti3 C2 Cl2 without metallic impurities. The T x surface terminations could be in situ modified from −Cl to −O and/or −S in this one‐pot process. The obtained −O‐terminated Ti3 C2 T x electrode exhibited a significant increase in capacity.